If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -1) + -2(x + -3) = 5x + 13 Reorder the terms: 3(-1 + 4x) + -2(x + -3) = 5x + 13 (-1 * 3 + 4x * 3) + -2(x + -3) = 5x + 13 (-3 + 12x) + -2(x + -3) = 5x + 13 Reorder the terms: -3 + 12x + -2(-3 + x) = 5x + 13 -3 + 12x + (-3 * -2 + x * -2) = 5x + 13 -3 + 12x + (6 + -2x) = 5x + 13 Reorder the terms: -3 + 6 + 12x + -2x = 5x + 13 Combine like terms: -3 + 6 = 3 3 + 12x + -2x = 5x + 13 Combine like terms: 12x + -2x = 10x 3 + 10x = 5x + 13 Reorder the terms: 3 + 10x = 13 + 5x Solving 3 + 10x = 13 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3 + 10x + -5x = 13 + 5x + -5x Combine like terms: 10x + -5x = 5x 3 + 5x = 13 + 5x + -5x Combine like terms: 5x + -5x = 0 3 + 5x = 13 + 0 3 + 5x = 13 Add '-3' to each side of the equation. 3 + -3 + 5x = 13 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 13 + -3 5x = 13 + -3 Combine like terms: 13 + -3 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| (2x-3)=(4x-1) | | -210=7(-6-5p)+7 | | -1(4n+5)=-15+1n | | -9x=15x+7+3x | | 5(w+7)-8w=32 | | -3+4x= | | (x/5)-(x/6)=(6/5) | | 2x-9=8y | | 7y-5=6y-5 | | 2x+4*3=72 | | (3x+2)=(x+3) | | -6n-7(1n-3)=35-6n | | 300-5=200+100 | | 5x+3xy=4-2y | | 8=-10x-6 | | 4+5=5+10 | | -26+4v=6(1+2v) | | 2x-3d+5c=c | | .667e=124 | | -x+11=8x-8 | | (5y+8)+3x=180 | | -3z+-4=6z-9z+6 | | 25x+2x-6=-35X+-7+10 | | -32+-4=6z-9z+6 | | 4x-15=10x+17 | | 12s^3+3s=0 | | 35+3p=45+2p | | A=-2(121)+362 | | 7x(x+4)(3x-2)=0 | | -8(1+6v)=-7v+33 | | X^2=2x+224 | | 0.055+0.045(9600-x)=465 |